Análisis regulatorio del etiquetado de protectores solares comercializados en Perú y propuesta de un reglamento técnico - Aranda Castro, Paul Esteban (2021)
The sanitary regulation of sun protection products differs from the countries where they are marketed, due to the fact that the existing regulatory framework adopts different criteria for their classification and requirements, before being placed on the market. The importance of sunscreens lies in the defense function it provides to the skin, against ultraviolet radiation (UV) and its potential adverse effects. At the national level, a variety of sunscreens are marketed in different cosmetic forms and at different prices, which present complex labels and with multiple benefits, however, the user does not clearly identify the relevant information to make a correct choice. The purpose of the investigation is to compare the requirements that correspond to the pertinent information that the labeling must carry out according to the requirements of each legislation such as the United States (FDA), European Union (COLIPA), Japan (JCIA) and Peru (CAN), in order to propose a sun protection regulation that guides its correct labeling. The results of this study will provide precise definitions for the discernment of the information provided on the labels in order to guarantee efficient protection against UV radiation; Thus, a proposal for national regulations on sunscreens in accordance with international standards and based on regulatory and scientific knowledge, will lead to responsible and preventive use by consumers, strengthening public health against UV radiation.